2015
DOI: 10.1136/bjsports-2015-094817
|View full text |Cite
|
Sign up to set email alerts
|

The acute:chronic workload ratio predicts injury: high chronic workload may decrease injury risk in elite rugby league players

Abstract: Aim Investigate whether acute workload (1 week total distance) and chronic workload (4-week average acute workload) predict injury in elite rugby league players. Methods Data were collected from 53 elite players over two rugby league seasons. The 'acute:chronic workload ratio' was calculated by dividing acute workload by chronic workload. A value of greater than 1 represented an acute workload greater than chronic workload. All workload data were classified into discrete ranges by z-scores. Results Compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
462
4
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(495 citation statements)
references
References 45 publications
22
462
4
7
Order By: Relevance
“…Given that the acute:chronic workload ratio derived from distance covered is associated with injury in rugby league players. 6 The present findings and the abovementioned studies provide evidence that researching contact-only workloads may be possible over acute and chronic periods, which could provide greater insight into collision injury risk.…”
Section: Discussionsupporting
confidence: 63%
“…Given that the acute:chronic workload ratio derived from distance covered is associated with injury in rugby league players. 6 The present findings and the abovementioned studies provide evidence that researching contact-only workloads may be possible over acute and chronic periods, which could provide greater insight into collision injury risk.…”
Section: Discussionsupporting
confidence: 63%
“…9 With the recent literature surrounding training load and injury risk in elite soccer, 14 a typical Yo-Yo IR1 benchmark of 2300 m 15 is a considerable distance, supplementary to the training load of a normal training week. As opposed to administering the Yo-Yo IR1, a more efficient, submaximal version has been utilised; the Yo-Yo Intermittent Recovery Test -submaximal (Yo-Yo IR1-sub).…”
Section: Introductionmentioning
confidence: 99%
“…Saw et al [13] found in their systematic review that athlete reported subjective information was highly sensitive to changes in athlete workload and physiological and psychological stress, so it is likely that these indings have some validity in demonstrating the athletes loading environment. Increases in acute training loads have been reported to signi icantly impact on the rate of injury [14]. This study has indicated that not on physical but cognitive loads should possibly be accounted for when assessing acute loading stress on the athlete.…”
Section: Relationship Issues 12% (2 Out Of 17)mentioning
confidence: 79%
“…The assessment and understanding of how these interactions create injury is beyond the scope of this case series and certainly requires further prospective study. What is apparent from this case series is ACL injury is unlikely to be related to a single factor, but a critical tipping factor might be loss of chronic training capacity or a perceived or actual increase in acute physical load [14].…”
Section: Relationship Issues 12% (2 Out Of 17)mentioning
confidence: 82%
See 1 more Smart Citation